2014
DOI: 10.1111/joor.12247
|View full text |Cite
|
Sign up to set email alerts
|

Force‐controlled biting alters postural control in bipedal and unipedal stance

Abstract: Human posture is characterised by inherent body sway which forces the sensory and motor systems to counter the destabilising oscillations. Although the potential of biting to increase postural stability has recently been reported, the mechanisms by which the craniomandibular system (CMS) and the motor systems for human postural control are functionally coupled are not yet fully understood. The purpose of our study was, therefore, to investigate the effect of submaximum biting on postural stability and on the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 51 publications
2
52
0
4
Order By: Relevance
“…First, in Ringhof et al [2] COP displacements were reported to be less under submaximum biting as compared to a mandibular rest position, i.e., nonbiting. Hence, the question remained whether these effects were the result of submaximum biting, in terms of decreased postural sway, or the result of nonbiting, in terms of increased postural sway.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…First, in Ringhof et al [2] COP displacements were reported to be less under submaximum biting as compared to a mandibular rest position, i.e., nonbiting. Hence, the question remained whether these effects were the result of submaximum biting, in terms of decreased postural sway, or the result of nonbiting, in terms of increased postural sway.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, submaximum clenching of the jaw was reported to significantly improve postural stability and to decrease the sway of cranial body segments in upright unperturbed stance [1][2][3]. The authors concluded that these improvements were induced by modulation of somatosensory input, particularly of the neck muscles [4], and facilitation of ankle extensor and flexor muscles [5,6], concomitant with attenuated reciprocal Ia inhibition [6].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Uma delas analisa se há efeito de mudanças na postura mandibular, na oclusão ou na contração voluntária dos músculos elevadores da mandíbula sobre a postura corporal/equilíbrio. Baseados nos resultados alguns autores afirmam que sim Milani et al, 2000;Takada et al, 2000;Yoshino;Higashi;Nakamura, 2003;Bracco;Deregibus;Piscetta, 2004;Bergamini et al, 2007;Sakaguchi et al, 2007;Tardieu et al, 2009;Cuccia, 2011;Ohlendorf et al, 2014;Iqbal, 2015a,b;Hellmann et al, 2015;Ringhof et al, 2015;, mas outros não Perinetti, 2006;Perinetti et al, 2010;Baldini et al, 2013;Marini et al, 2013).…”
Section: Lista Deunclassified